The effect of LILRB1 but not LILRA3 gene polymorphism in immunopathology of ankylosing spondylitis—A parallel to KIR genes. (20th March 2019) - Majorczyk, Edyta; Wiśniewski, Andrzej; Zoń‐Giebel, Aleksandra; Chlebicki, Arkadiusz; Wiland, Piotr; Kuśnierczyk, Piotr
Abstract: LILR and KIR receptors recognize HLA‐B27 and may influence immune response in ankylosing spondylitis (AS) development. Purpose of the study was to analyse LILRB1 / LILRA3 polymorphisms in AS. We observed a possible protective effect of the T allele of LILRB1 rs1061680:T>C and no association with insertion/deletion polymorphisms of LILRA3 with AS.